2014
DOI: 10.1039/c4cp00503a
|View full text |Cite
|
Sign up to set email alerts
|

How a protein can remain stable in a solvent with high content of urea: insights from molecular dynamics simulation of Candida antarctica lipase B in urea : choline chloride deep eutectic solvent

Abstract: Deep eutectic solvents (DESs) are utilized as green and inexpensive alternatives to classical ionic liquids. It has been known that some of DESs can be used as solvent in the enzymatic reactions to obtain very green chemical processes. DESs are quite poorly understood at the molecular level. Moreover, we do not know much about the enzyme microstructure in such systems. For example, how some hydrolase can remain active and stable in a deep eutectic solvent including 9 M of urea? In this study, the molecular dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
158
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 205 publications
(167 citation statements)
references
References 56 publications
(64 reference statements)
8
158
1
Order By: Relevance
“…[62] We found, in our earlier simulation works that one of the initial regions, which decomposed by exposing to scCO 2 and urea 8M is helix5. [63,64] Other researcher have obtained similar result about that and found that modifying helix5 leads to obtaining more active and stable enzymes [62]. Here, we found that carboxylation of Lys 136 can stabilize helix5 from denaturation in scCO 2 .…”
Section: Carboxylation Of Lysinessupporting
confidence: 86%
“…[62] We found, in our earlier simulation works that one of the initial regions, which decomposed by exposing to scCO 2 and urea 8M is helix5. [63,64] Other researcher have obtained similar result about that and found that modifying helix5 leads to obtaining more active and stable enzymes [62]. Here, we found that carboxylation of Lys 136 can stabilize helix5 from denaturation in scCO 2 .…”
Section: Carboxylation Of Lysinessupporting
confidence: 86%
“…It is also necessary to consider the ratio of HBA/HBD, which might affect the solvatochromic parameters and the hydrogen bond formation between the reaction mixtures (Kim et al 2016). A molecular dynamics simulation of lipase in ChCl/U firstly proved that the hydrogen bond between DES components could hinder the attack of U to the enzyme function domains, thus resulting in a stabilized enzyme (Monhemi et al 2014). …”
Section: Influence Of Dess On Biocatalysismentioning
confidence: 99%
“…with cholinium chloride) whereas its concentration is much more higher [11]. It was found that constituents of the DES form an important non-covalent complex that limit their diffusion to the protein core [12,13]. The DES forms hydrogenbonds with the surface residues of the enzyme which, instead of lipase denaturation, lead to greater enzyme stability.…”
Section: From Eutectic To Deep Eutectic Solvents (Des)mentioning
confidence: 96%